44.6k views
3 votes
105x^6y^5+70x^7y^11/35x^7y^4

User Benleung
by
6.0k points

1 Answer

3 votes

Answer:


3(y)/(x) + 2y^(7)

Explanation:

We have to simplify the expression as given below:


(105x^(6)y^(5) + 70x^(7)y^(11))/(35x^(7)y^(4)  )

As we know that
(a + b)/(c) = (a)/(c)  + (b)/(c)

=
(105x^(6)y^(5))/(35x^(7)y^(4)) + (70x^(7)y^(11))/(35x^(7)y^(4))

As we know the property of exponent
(x^(a) )/(x^(b) ) = x^(a - b)

=
3x^(6 - 7)y^(5 - 4)  + 2x^(7 - 7) y^(11 - 4)

=
3x^(-1)y^(1) + 2x^(0) y^(7)

As we know the properties of exponents
a^(-b) = (1)/(a^(b) ) and
a^(0) = 1

=
3(y)/(x) + 2y^(7) (Answer)

User DorianFM
by
5.2k points